Antibacterial Activity of Medicinal Plant Crateava nurvala (bark) against Bacterial Strains Causing Urinary Tract Infection - Chandra, S.; Gupta, C.P. (Asian Journal of Chemistry, 2010)
Bacterial strains EC1, KL1 and PS1 used in the present study were isolated from patient's urine, suffering from urinary tract infection (U.T.I.) and were characterized as E. coli, Klebsiella sp. and Pseudomonas sp. respectively. Antibacterial activities in crude extract of bark Crateava nurvala (varuna) plant were tested against bacterial strains in vitro. The maximum growth inhibition by the crude extract was recorded against E. coli followed by Pseudomonas sp. and Klebsiella sp. after 48 h incubation at 28 ± 1°C being of 35.3 mm, 28.4 mm and 18.6 mm diameter respectively. As far as antibiotic sensitivity was concerned E. coli was maximum inhibited by amikacin, Klebsiella sp. and Pseudomonas sp. by ciprofloxacin, inhibition rone being 38.1 mm, 40.5 mm and 27.2 mm respectively after 24 h at 28 ± 1°C.